Unlocking the Nutraceutical Potential of Legumes and Their By-Products: Paving the Way for the Circular Economy in the Agri-Food Industry - Fanghua Guo; Renan Danielski; Sarusha Santhiravel; Fereidoon Shahidi (MDPI AG, 2024)
Legumes, including beans, peas, chickpeas, and lentils, are cultivated worldwide and serve as important components of a balanced and nutritious diet. Each legume variety contains unique levels of protein, starch, fiber, lipids, minerals, and vitamins, with potential applications in various industries. By-products such as hulls, rich in bioactive compounds, offer promise for value-added utilization and health-focused product development. Various extraction methods are employed to enhance protein extraction rates from legume by-products, finding applications in various foods such as meat analogs, breads, and desserts. Moreover, essential fatty acids, carotenoids, tocols, and polyphenols are abundant in several residual fractions from legumes. These bioactive classes are linked to reduced incidence of cardiovascular diseases, chronic inflammation, some cancers, obesity, and type 2 diabetes, among other relevant health conditions. The present contribution provides a comprehensive review of the nutritional and bioactive composition of major legumes and their by-products. Additionally, the bioaccessibility and bioavailability aspects of legume consumption, as well as in vitro and in vivo evidence of their health effects are addressed.